MENUMBUHKAN KREATIVITAS SISWA SEKOLAH DASAR MELALUI PEMBUATAN CANVA E-COMIC DALAM PEMBELAJARAN ILMU PENGETAHUAN SOSIAL - Cusni Anjani; Leny Vitriasari; Rahma Nur Ainunnasya; Bunyamin Maftuh (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2023)
This study aims to obtain information about the creativity of elementary school children through making e-comics in the Canva application in Social Sciences (IPS) learning. This study uses a qualitative descriptive research method. The research subjects were grade 3 students at SDN 086 Cimincrang, Bandung City. Data collection techniques were carried out by means of questionnaires, observation, interviews and documentation. The data analysis carried out consisted of data collection, data reduction, data display, and data verification. The results of the study show that students are very creative in creating e-comics through the Canva application. This is evidenced by the work of making e-comics created by grade 3 students at SDN 086 Cimincrang, which are very diverse and original. From this learning students are motivated to improve learning outcomes through digital comics in social studies lessons. Thus it can be concluded from the calculation of students' e-comic scores through the results of questionnaires, interviews and field observations showing that making canva e-comics for elementary school students has a good influence on learning, especially in social studies lessons.